Effect of Healthy Eating Habits on the Academic Performance of Graduating Students - Sohail Imran Khan; Rohat Zada; Dhuha Saad Ismael (ACHSM, 2022)
Introduction: This study was necessary as most graduating students were studying hard but, it didn't work as expected, leading to disappointment. When they move to undergraduate courses, their lifestyle gets changed. Therefore, it is relevant based on their diet, it can help them achieve higher academic performance. Objective: The present research work was undertaken to examine the effect of a healthy diet on the overall academic performance of graduating students. Methods: For the study, 279 students from RTM Nagpur University were used as sample size and were selected randomly. A structured questionnaire was used to collect the responses from the participants. Students were evaluated based on their SGPA scores. Results: Results obtained state a strong and positive association between a healthy diet and academic performance. Results confirmed the hypothesis that if students practice of daily healthy diet their academic performance will improve. Conclusion: Many students of this university have habits of skipping breakfast or taking it a few times a week and not daily. Also, they are not good at eating healthy foods. This directly affects their performance in academics. Therefore, parents are advised to keep a strict check on these habits.